Organizational justice and cynicism: a mixed method study at schools - Hüseyin Akar; O. Tayyar Çelik (Institute of Advanced Engineering and Science, 2019)
This study aimed to investigate the relationship between organizational justice and cynicism at school organizations. Thus, explanatory sequential research design, in which both qualitative and quantitative methods are used, has been used. Under the quantitative part, meta-analysis has been used so that 159 studies consist of articles and dissertations about cynicism being done within Turkey have been reached throughout literature. With further enquiries, it was found that 16 of them include the relationship between organizational justice and cynicism. Considering inclusion criteria, eight studies which include necessary data for the relationship between organizational justice and cynicism were put into meta-analysis step. However, in the qualitative part, the research was designed through phenomenological research design in which 17 teachers, chosen in terms of maximum-variation sampling strategy, were interviewed via a semi-structured interviewing form. The results revealed that teachers' perceptions for organization justice have a strong but negative effect on their likelihood to experience cynicism while it was also found that publication type is not a proper moderator on effect size. On the other hand, within the qualitative analysis, it was found that teachers develop negative beliefs against school, managers and teachers; experience feelings such as anger, distrust, sadness, hatred and alienation and thus criticize school and managers, behave recklessly and opponent as a result of unfair practices.